2015
DOI: 10.1038/npp.2015.7
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Resting State fMRI Activity Predicts Processing Speed Deficits in First-Episode Psychosis

Abstract: Little is known regarding the neuropsychological significance of resting state functional magnetic resonance imaging (rs-fMRI) activity early in the course of psychosis. Moreover, no studies have used different approaches for analysis of rs-fMRI activity and examined gray matter thickness in the same cohort. In this study, 41 patients experiencing a first-episode of psychosis (including N ¼ 17 who were antipsychotic drug-naive at the time of scanning) and 41 individually age-and sex-matched healthy volunteers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
3

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(13 citation statements)
references
References 63 publications
0
10
3
Order By: Relevance
“…Though valuable information would be evident using larger ROIs, such methods do not exclude the possibility that some more focused abnormalities could be missed, as reported (Argyelan et al, 2015). By contrast, we adopted several advanced feature selection approaches, including ReliefF and CFS, to mine from tens of thousands of brain voxels efficiently, and the comparisons in Table 3 did show advantages of the proposed method.…”
Section: Discussionmentioning
confidence: 98%
“…Though valuable information would be evident using larger ROIs, such methods do not exclude the possibility that some more focused abnormalities could be missed, as reported (Argyelan et al, 2015). By contrast, we adopted several advanced feature selection approaches, including ReliefF and CFS, to mine from tens of thousands of brain voxels efficiently, and the comparisons in Table 3 did show advantages of the proposed method.…”
Section: Discussionmentioning
confidence: 98%
“…Specifically, Satterthwaite et al (2016) showed altered frontal cortex in youth with psychosis spectrum disorders. Moreover, similarly to schizophrenia, altered structural (Luck et al, 2011;Price et al, 2008) and functional (Alonso-Solís et al, 2012;Argyelan et al, 2015;Fornito et al, 2013;Schmidt et al, 2013) PFC connectivity has also been reported for FEP. Therefore, despite the presence of inconsistencies in the available literature, our study suggests that altered GI and, consequently, disrupted PFC connectivity represents an indirect developmental marker for psychosis, overcoming the categorical diagnosis of schizophrenia (White and Gottesman, 2012), in line with a dimensional approach as per the Research Domain Criteria approach (Cuthbert and Insel, 2010).…”
Section: Discussionmentioning
confidence: 99%
“…Algorithmic classifiers have been successfully applied in several neurodegenerative disorders using structural [22,23] and functional [24][25][26] magnetic resonance imaging (fMRI) measures. Machine learning and fMRI voxel-wise multivariate classification were implemented as powerful tools for decoding neural representations of thoughts or physical objects at a particular time-point [27][28][29], with the LDA being validated in both normal [30][31][32][33] and disordered [34][35][36][37] states.…”
Section: Introductionmentioning
confidence: 99%